Transgenders in India: an Introduction - Mishra Veerendra (New York Routledge, 2024)
This introductory volume studies the challenges faced by the transgender community in India. It traces the history of the representation of the community in Hindu texts to understand the evolution of their status within Indian society. The book looks at various themes such as the concept of establishing identity through the processes of 'coming out' and 'transitioning' and analyses how race, ethnicity, sexual orientation, class, nation, religion, and ability have cross-influenced to shape the transgender experience and trans culture across and beyond the binary.
Keywords: Transgender people-India; Transphobia-people; Gender